2022
DOI: 10.1136/neurintsurg-2022-018801
|View full text |Cite
|
Sign up to set email alerts
|

Revision balloon kyphoplasty and vertebra-pediculoplasty using cannulated screws for osteoporotic vertebral fractures with cement dislodgement following conventional balloon kyphoplasty

Abstract: We report the usefulness of revision balloon kyphoplasty (re-BKP) and vertebra-pediculoplasty using cannulated screws (VPCS) for osteoporotic vertebral fractures (OVF) following cement dislodgement of conventional BKP. Between 2015 and 2020, three patients with OVF developed symptomatic cement dislodgement following BKP and underwent re-BKP. All three patients showed a loose cemented mass and spinal instability. Balloon inflation was performed in the gap between the loosened cemented mass and the remaining cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Yonezawa et al 14) reported revision BKP and pediculoplasty using cannulated screws could be an effective technique to stabilize the OCFs with cement dislodgement after failed BKP instead of highly invasive instrumentation surgery. Based on our findings, we do not recommend BKP for Kummell’s disease and cement-augmented screw fixation may be effective for these kinds of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Yonezawa et al 14) reported revision BKP and pediculoplasty using cannulated screws could be an effective technique to stabilize the OCFs with cement dislodgement after failed BKP instead of highly invasive instrumentation surgery. Based on our findings, we do not recommend BKP for Kummell’s disease and cement-augmented screw fixation may be effective for these kinds of fractures.…”
Section: Discussionmentioning
confidence: 99%